An Objectional Offence: A Critique of the Possession Offence in the Films, Videos, and Publications Classification Act 1993 - Knight, Dean R (Victoria University of Wellington Law Review, 1997)
This article examines the strict liability offence of the possession of objectionable publications in s 131 of the Films, Videos, and Publications Classifications Act 1993 ("FVPCA"). The use of strict liability in relation to the possession offence was criticised during the passing of the FVPCA. This article explores fully the criticisms that can be made about the use of strict liability generally, specifically in the context of censorship legislation.